Results of salmon fishery in the Far-Eastern fishery basin in 2022 - V. A. Belyaev; A. N. Kanzeparova (Известия ТИНРО, 2023)
Data on forecasted catch, actual catch and their ratio are presented for the main species of pacific salmon; the salmon fishery in 2022 is analyzed. The forecast of the salmon annual catch in the Far-Eastern fishery basin for 2022 should be recognized as generally satisfactory (reliability of 84.6 %).